Karakterisasi, Pengaruh Sumber Nitrogen dan Karbon terhadap Produktivitas Enzim Lipase Rhizopus microsporus var oligosporus UICC 550 - Mangunwardoyo, Wibowo; Lusini, Yuyun; Gandjar, Indrawati (Universitas Atma Jaya Yogyakarta, 2009)
Effect of nitrogen and carbon source on the production of extracellular lipase by R.microsporus var. oligosporus UICC 550 was studied. The enzyme activity was alsocharacterized in terms of temperature, pH, stability at room temperature, and effectof divalent ion. The amount of 2.5% (w/v) of olive oil as carbon sources and 5% (w/v)peptone as nitrogen sources were the optimum for production of lipase enzyme.Partial purifications using ammonium sulfate followed by dialysis showed that at pH6.5 and temperature 35oC was the optimum condition, respectively. The stability(remaining up to 80% of the optimum enzyme) was recorded at pH 6.5 after 24 hoursincubation at room temperature. The optimum activity remained 40% of the after onehour incubation at 35oC. Divalent ions concentration at 1 mM, Zn2+, Cu2+, Mg2+ andFe2+ inhibited the lipolytic activity.